Identification of cost data input problems in life cycle cost analysis and the mitigation strategies - Ayob, Mohd Fairullazi; Abdul Rashid, Khairuddin (2014)
The objective of this paper is to present the identification of problems and mitigation strategies associated with data input of LCC estimation for building works in the Malaysian construction industry. The focus of quality data here is cost data inputs of building LCC. This paper reports part of a three-year research programme to enhance quality of LCC outputs through the enhancement of quality data input requirements. A modified Delphi approach was carried out to generate consensus of expert opinion regarding the state quality degree of data as inputs for LCC and appropriate strategies to mitigate the problems associated with data input of LCC by evaluating opinions and judgments from a group of experts that have experience, skills and knowledge in LCC. The modified Delphi study has established that there is limited availability and inaccessibility of current and reliable cost data input of LCC analysis for building works in the Malaysian construction industry. Looking at the results of the most appropriate strategies which have been prioritized, there is an overwhelming requirement for a clear procedure or comprehensive guideline to be prepared on the acquisition of cost data inputs to enhance quality data input requirements of LCC. This clear procedure can be best translated in the form of model, framework or protocol to be developed so that a step by step methodological approach can be exacted to make the data available, accessible, current and reliable in facilitating the clients, estimators and researchers to better calculate LCC leading to better outputs.